What Can We Learn about Country Performance from Conditional Comparisons across Countries? - Ravallion, Martin, 1952- 1952- (The World Bank, 1999)
May 2000 - Existing methods for assessing latent country or institutional performance can yield deceptive results. There have been many attempts to infer latent performance attributes of governments (or other institutions) from conditional comparisons that control for observed variables. Success in doing so could greatly improve government performance. Ravallion critically reviews the econometric foundations of the methods used. He argues that latent heterogeneity remains a fundamental but unresolved problem. Locating a benchmark for measuring performance adds a further problem. Current methods do not yield a consistent estimate of even the mean latent performance attribute. An assessment of country performance by these methods could well be wildly wrong. This paper - a product of Poverty and Human Resources, Development Research Group - is part of a larger effort in the group to assess and improve methods for monitoring and assessing country performance. The study was funded by the Bank's Research Support Budget under the research project Policies for Poor Areas (RPO 681-39). The author may be contacted at mravallion@worldbank.org